2022
DOI: 10.3390/pathogens11030293
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Agents against Flavivirus Protease: Prospect and Future Direction

Abstract: Flaviviruses cause a significant amount of mortality and morbidity, especially in regions where they are endemic. A recent example is the outbreak of Zika virus throughout the world. Development of antiviral drugs against different viral targets is as important as the development of vaccines. During viral replication, a single polyprotein precursor (PP) is produced and further cleaved into individual proteins by a viral NS2B-NS3 protease complex together with host proteases. Flavivirus protease is one of the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…In 2016, the ZIKV was classified as a severe disease due to of its effects on newborns. , Most viruses in this family have similar structures; however, there is no specific drug to treat any of them. , Therefore, it is necessary to accelerate the methods of drug discovery and development. The traditional approach involves synthesizing compounds and testing them, which is a trial-and-error process. , The use of chemoinformatic techniques, such as the PTML method, can accelerate the discovery of potential drug candidates that can inhibit the development of this type of virus.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, the ZIKV was classified as a severe disease due to of its effects on newborns. , Most viruses in this family have similar structures; however, there is no specific drug to treat any of them. , Therefore, it is necessary to accelerate the methods of drug discovery and development. The traditional approach involves synthesizing compounds and testing them, which is a trial-and-error process. , The use of chemoinformatic techniques, such as the PTML method, can accelerate the discovery of potential drug candidates that can inhibit the development of this type of virus.…”
Section: Introductionmentioning
confidence: 99%
“…Highly conserved among flaviviruses, it is an essential enzyme in virus replication. Given its essential role, the NS2B/NS3 proteases (NS2B/NS3 pro ) of flaviviruses are promising drug targets; for example, DENV2, YFV, WNV, and ZIKV NS2B/NS3 pros present high amino acids sequence conservation and all four have the same structural fold, which confers a similar substrate specificity profile [ 16 , 17 ]. Due to their importance, we selected all four viruses to study the effect of a bioactive plant derivative molecule against NS2B/NS3 pro .…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was reported that niclosamide, an anthelminthic drug, which is historically used to treat tapeworm infection, could be repurposed for use against SARS-CoV-2 ( Garrett et al, 2021 ). Previously our lab was working on niclosamide and its derivatives as potent inhibitors against flaviviruses ( Li et al, 2020b ; Samrat et al, 2022 ; Xu et al, 2020c ). It has been shown that niclosamide suppressed the cytopathic effect (CPE) of SARS-CoV at a concentration of as low as 1 μM and inhibited SARS-CoV replication with an EC 50 value of less than 0.1 μM in Vero E6 cells ( Xu et al, 2020c ).…”
Section: Introductionmentioning
confidence: 99%